The functional outcome of metacarpal fractures fixed with mini plates and screws - Gopinathan, Abhijith; Abdin, Nadir Shajan; Varghese, Ibin; Jose, Jerin (International Surgery Journal, 2026)
Background: Metacarpal fractures are common hand injuries that can significantly impair hand function if inadequately treated. Surgical fixation using mini plates and screws provides stable fixation and permits early mobilization, which may improve functional outcomes. However, evidence regarding procedure-specific functional outcomes remains variable. Methods: This prospective observational study was conducted in the Department of Orthopaedics at Government Medical College, Kottayam, over a one-year period from 1st January 2025 to 31st January 2026. A total of 47 adult patients with metacarpal fractures requiring surgical intervention were included. All patients underwent open reduction and internal fixation using mini plates and screws. Functional outcome was assessed using the Total Active Flexion (TAF) score at 10 weeks, 3 months, and 6 months postoperatively. Pain was evaluated using the Visual Analogue Scale (VAS), and radiological union was assessed using serial X-rays. Statistical analysis was performed using SPSS version 26, with p<0.05 considered statistically significant. Results: The mean age of patients was 34.6±9.9 years, with a male predominance (37;78.7%). Metacarpal shaft fractures were the most common injury (37;78.7%). Radiological union was achieved in all patients (47;100%) by 6 weeks. Functional outcomes improved significantly over time, with excellent TAF scores observed in 42 patients (89.4%) at 6 months (p<0.01). Postoperative pain reduced markedly, with 46 patients (97.9%) being pain free at 6 months (p<0.01). Conclusions: Mini plate and screw fixation of metacarpal fractures provides reliable fracture union, excellent functional outcomes, and significant pain relief, making it an effective treatment option for unstable metacarpal fractures.